Orientation to the image, an old problem that evokes the crisis in the search for the legitimacy of the essence of art. (Quaestiones Disputatae: temas en debate, 2022)
This paper addresses the problem of the limits of image interpretation. The basic question is whether or not it is possible to orient ourselves to it and, if so, in what way we can do so. On the one hand, the analysis of this question has as its central theme the conception of art history as a concrete knowledge about images. On the other hand, it presupposes the idea that art history needs to be rethought, because artistic images cannot be fully encompassed by a presumed knowledge, since they are also inhabited by irrationality, doubt and even some temporal gaps that allow us to conclude that it is pretentious to generate a historical tone that affirms an exact epistemology of art. Thus, this epistemological and aesthetic problem will be approached through the theories of Panofsky, Heidegger and Didi-Huberman.
Keywords: art, image, interpretation, art history, epistemology of art.